Participatory Action Research dalam Pembelajaran Kimia Abad 21: Pengembangan Rencana Pelaksanaan Pembelajaran Bercirikan PCK - Kartyka Nababan; Sofia Krisen (Chemistry Department, Universitas Negeri Manado, 2023)
Participatory Action Research the development of a learning implementation plan characterized by pedagogical content knowledge is research involving chemistry teachers who directly experience the real conditions of learning. The resulting lesson plan is relevant to use in the same environment as the learning nature setting, for example online, offline, and blended. Device development is carried out through a cycle through at least four main steps; (1) RPP device development; (2) field tests; (3) evaluation; and (4) reflection. Input factors (input) in the development are: (1) the experience of teachers; (2) knowledge of the learning process; (3) theory and reflection methods; (4) scientific in educators; and (5) intuition and creativity of teachers. While the products produced are (1) 21st-century PCK lesson plans; (2) knowledge of 21st-century chemistry teaching; (3) Process Quality Improvement; (4) trained teachers; and (5) new concepts and teaching materials.